"It's About Us, You Know?" Relapse in Emotionally Focused Couples Therapy for Addictions. Issue 4 (2nd October 2018) - Fletcher, Kara; Macintosh, Heather
Abstract : Addiction treatment unavoidably entails working with relapse. In the context of couple therapy, discussion of relapse can become an integral part of the treatment process, as each partner is affected and interprets relapse differently. Drawing on data from a case study that used a theoretical extension of emotionally focused therapy for couples dealing with substance addictions, this article analyzes the experiences of slips and relapse across 4 couples. Using a thematic analysis to explore the findings, 4 primary themes are identified related to slips and relapse within the context of couple therapy and additions. These themes include guilt, shame, and depression; relapse as an attachment injury; confusion about relapse; and relapse as part of the process. Recommendations are offered for treating and working with relapse in the context of couple therapy.